Pengaruh Akses Teknologi, Infrastruktur Digital, Pendidikan, dan Ketersediaan Pekerjaan terhadap Kesejahteraan Masyarakat: Model Mediasi Ketahanan Ekonomi dan Moderasi Kualitas Sumber Daya Manusia - Dassucik, Dassucik; Hafas Rasyidi, Ahmad; Sukrisno Sugeng, Irwin; Nikmah, Ulin (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
This study explores the impact of key factors such as technology access, digital infrastructure, education, and job availability on community well-being in East Java, Indonesia, with a focus on economic resilience as a mediating variable and human resource quality as a moderating factor. This study uses data obtained from 300 respondents, specifically social assistance recipients in East Java, selected through purposive sampling. Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to analyze the relationship between these factors. The findings indicate that digital infrastructure, education, and job availability significantly influence economic resilience and community well-being. Economic resilience plays a significant role in mediating these effects, while human resource quality moderates the relationship, enhancing the impact of economic resilience on well-being. This study contributes to the literature by integrating these variables into a comprehensive framework, emphasizing the need for investment in education, digital infrastructure, and inclusive job creation policies to address the welfare gap, particularly in rural areas, and to promote sustainable development in East Java.